HUBUNGAN POLA ASUH MAKAN BALITA DENGAN STATUS GIZI BALITA - Wardani, Puspita; Setya Arum, Dyah Noviawati; Zein, Asmar Yetti (Jurnal Kesehatan Ibu dan Anak, 2015)
The severe underweight in Yogyakarta regency 2011 is 1,35%. Gedongtengen subdistrict have biggest severe underweight that 26 from 977 children (2,6 %) and moderate underweight 120 children (12,78 %). Pringgokusuman village has the biggest severe underweight is about 2,15% and moderate underweight about 18,26%. Child nutritional status can be influenced by childcare eating patterns. To solving the nutritional problem, not sufficiently resolved by medical but also childcare eating patterns can support the creationof healthy behavior. The purpose is to examine the relationship between childcare eating pattern with child nutrition status in Pringgokusuman village 2013. The kind of research is observational with a cross-sectional design, and the sampling technique is proportional sampling. Research location in Pringgokusuman village, Gedongtengen subdistrict. The respondents are mothers and children aged 12-59 months as much as 63 samples. Research instrument by questionnaire and steelyard with a level of accuracy 0,1 kg. The relation between the variables is analyzed by the Kendall Tau test. The result of the Kendall Tau test concerning the value of 0,03 <0,05. There is a relationship between childcare eating pattern with child nutrition status in Pringgokusuman village in 2013